Implementasi Ilmu Ushul Fiqih dalam Pembelajaran Siswa di Madrasah Ibtidaiyah (MI) - Masyhadi Masyhadi (LP3M STITNU AL HIKMAH MOJOKERTO, 2021)
Fiqh at Madrasah Ibtidaiyah aims to equip students to know and understand the basics of Islamic law in detail and comprehensively, both in the form of naqli and aqli arguments. directed to prepare students to recognize, understand, appreciate and practice Islamic law, which then becomes the basis of their way of life through guidance, teaching, practice using experience and habituation. The purpose of this research is to explain the implementation of ushul fiqh in student learning at Madrasah Ibtidaiyah (MI). The method in this study uses a qualitative method with the type of descriptive analytic research. The results in this study that the quality of learning affects the learning outcomes. Learning the science of ushul fiqh is included in the Islamic Religious Education group in terms of Syara' law and guides students towards the emergence of beliefs and the truth of these laws and forms a habit to implement them. Thus, the implementation of fiqh lessons at Madrasah Ibtidaiyah certainly does not specialize in one area of ​​the division, but the discussion has been adapted to the needs of students and what is experienced and needed in everyday life.